A case of Canavan disease with normocephaly - A rare entity - Hassan, Shamsuddin; Bajaj, Srilatha; Meena, Sangeeta; Mina, Shyam Sundar (Indian Journal of Child Health, 2017)
Canavan disease (CD) is an autosomal recessive disorder with spongy degeneration of white matter of the brain. It typically presents with developmental delay, visual problems, and macrocephaly. Our patient presented with these features along with normocephaly. Brain magnetic resonance spectroscopy showed typical findings for CD (peaks of N-acetylaspartic acid). This case illustrates the fact that the presence of normocephaly should not be used in isolation to rule out the possibility of CD.